Beneficiosa o no beneficiosa la evaluación pre- ocupacional - Cachi-Piña, Isabelita Cristina; Gil-Campos, Milagros; Ramírez-Ramírez, Wilson Enrique; Tello-Vera, Stalin (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2019)
Carta al Editor (sin resumen)